How the macroeconomic context impacts on attitudes to immigration: evidence from parallel time series - Joakim Ruist (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
This study investigates the effects of the macroeconomic context on attitudes to immigration. Earlier studies do in most cases not provide significant empirical support for the existence of important such effects. In this article it is argued that this lack of consistent evidence is mainly due to the cross-national setup of these studies being vulnerable to estimation bias caused by country-specific factors. The present study instead analyzes attitude variation within countries over time, using parallel time series from 23 European countries that were observed biannually 2002-2012 in the European Social Survey. The results provide firm empirical support in favor of macroeconomic variation importantly affecting attitudes to immigration. As an illustration, the estimates indicate that the number of individuals in the average European country in 2012 who were against all immigration from poorer countries or of foreign ethnicities was 40% higher than it would have been if macroeconomic conditions in that year had been as good as they were in 2006.
Keywords: F22; E32; J15; 330; attitudes; immigration; macroeconomics; time series